Spin transport properties of T-phase VSe2 2D materials based on eight-atom-ring line defects - Xuelian Sun; Xinxin Jiang; Zhikuan Wang; Xuhui Xu; Lei Yang; Quan Gao; Dongmei Li; Bin Cui; Desheng Liu (Results in Physics, 2023)
Defects play a crucial role in modulating the properties of solid-state materials by inducing localized states that often benefit magnetic moments. Recently, direct experimental observations have shown the appearance of bunches of eight-atom-ring line defects in the T-phase VSe2 monolayer, a remarkable room-temperature two-dimensional magnetic metal. Using first-principles calculations, we have found that these line defects could enhance the magnetic moments, and half-metallicity (nearly 100% spin polarization) can be achieved in the structure with the densest defects. Furthermore, our analysis of the partial charge density distribution shows that a closer inter-defect distance between the d-states of vanadium atoms and p-states of selenium atoms increases the penalty of electrons occupying the spin-minority states. Moreover, we have discovered the high conductivity channel exhibits negative differential resistance characteristics within a bias range of 0.2 to 0.4 V (–0.4 to –0.2 V). Our findings broaden the scope of the applications of two-dimensional materials in spintronics and provide some theoretical guidance for the design of high-performance spintronic devices.